Association Between Nutritional Status and Physical Activity Among Reproductive Age Women in Arba Minch Health and Demographic Surveillance Site, Southern Ethiopia - Darik Temesgen Assefa; Dessalegn Ajema Berbada; Melesse Mengesha Merkina; Desta Haftu Hayelom; Nigus Kabtu Belete; Simegn Wagaye Kefene; Befikadu Tariku Gutema (International Journal of Public Health)
ObjectivesReproductive age women in Ethiopia face significant double burden malnutrition. Although underweight prevalence has declined, overweight and obesity rates are raising due to rapid nutrition transitions and physical activity levels changes. This study aimed to assess the association between nutritional status and physical activity among these women.MethodsCommunity-based cross-sectional study was conducted in Arba Minch Health and Demographic Surveillance Site involving 422 randomly selected women from April to May 2022. Data were collected through interviews, including weight and height measurements. Multinomial logistic regression assessed associations, with significance at p < 0.05.ResultApproximately 20.1% women faced malnutrition with 7.8% underweight and 12.3% overweight/obesity. Notably, 84.6% engaging in ≥600 MET-minutes of physical activity weekly and inactive women were 2.8 times more likely to be overweight/obese. Significant associations were found between nutritional status and factors like educational status, contraceptive use, household food insecurity, and family size.ConclusionIncreased overweight/obesity risk among inactive women underscores the need for promoting active lifestyles and targeted interventions for better health.